Pouk književnosti v hrvaški gimnaziji - Benjak, Mirjana (Jezik in slovstvo, 2000)
In the last ten years, Croatia has seen a number of major changes (political, democratic, economic, etc.), which have been reflected also in (secundary) education. Today, Croatia's secundary educational system pursues aims directedtowards humanistic and democratically pluralized education. Several (practical) measures have been introduced, from changes in school legislation to less loaded curricula. However, there is still no theoretically coherent model of a new Croatian school, with which the country could join the Europeaneducational system. Commitment to a national school of European orientation has not gone beyond the stage of verbal declarations. It is therefore impossible to talk about any significant systemic provisions in documents related to secundary schools, including teaching literature in them. Thus the article focuses on those factors that make part of practical implementation of the concept of new education, vis. (grammar-school) curricula and readers/textbooks.
Keywords: pouk književnosti; srednje šole; gimnazije; Hrvaška; Croatia; učni načrti; učbeniki